Evaluation of the market systems development approach: Lessons for exp anded use and adaptive management at Sida Volume I: Evaluation Report - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Sida, 2018)
This report presents the findings of an evaluation of Sida’s managemen t of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD prog rams. Beyond this, it provides insights relevant to Sida’s wider suppo rt to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive condition s are in place for effective MSD programs and good development program ming more generally. Sida’s relatively flexible framework of rules, gu idelines and systems for project management provide the space needed f or staff to innovate and manage adaptively. But for this to happen con sistently and effectively, Sida needs to invest more deliberately in b uilding the capacity of its staff in relevant areas. In addition, lead ership and incentives are key to shaping a culture of active experimen tation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and st rengthened oversight of project performance, including through adjustm ents to Sida’s contracts and funding agreements.